(untitled) (AUN INTERNATIONAL CONFERENCE, 2025)
Artificial intelligence (AI) is rapidly influencing governance across Africa, yet dominant ethical frameworks remain rooted in Western contexts. This raise concerns around data sovereignty, cultural misrepresentation, and the marginalization of indigenous knowledge systems (IKS). Using a decolonial and critical AI ethics lens, this paper examines how African values, epistemologies, and governance structures can shape responsible AI. It argues for moving beyond imported checklists toward sovereignty, inclusivity, and epistemic plurality. A conceptual framework is proposed, positioning data sovereignty and IKS as core anchors, supported by participatory design, epistemic justice, and accountability, and operationalized through policy, institutional capacity, and technological adaptation. The framework highlights outcomes of ethical AI practices, reduced digital colonialism, and culturally aligned innovation, with policy implications for stronger data governance and institutional capacity-building.